OPERATING RESULTS OF SILAGE ENTERPRISE OF A FARM - A CASE STUDY - Kovács, Evelin; Sulyok, Dénes; Czakó, Iván; Kovács, Krisztián; Felföldi, János (Applied Studies in Agribusiness and Commerce, 2023)
Improvements in agriculture has been focusing on innovations to improve the efficiency of the activity by making the traditional production structure currently in use more flexible and by making the necessary technological changes for farmers with large areas and the necessary machinery and equipment. Farms with significant arable land are able to offset the effects of changes affecting efficiency and profitability. The decisive sector of agriculture in Hungary is crop production, therefore its performance is largely determined by the annual output of the crop sector and the volatility in prices. From the farm data, we calculated farm-level results that support the need for machinery modernisation efforts, as precision tools and improvements already started in maize production can be applied fruitfully even in the light of the increasing frequency of negative climatic effects. During the development of silage maize cultivation technology, the achievements of precision farming were applied. Differentiated nutrient replenishment and sowing operations were used, in addition to the fact that harvesting was also documented. We set ourselves the goal of analyzing the management data of the study period between 2019-2022 in order to reveal the nature of the changes that occurred in terms of production value, production cost, and income, as well as the components that shape them. The presented values ​​are average values ​​of such conditions which are also suitable for crop-level conclusions. At the same time, they can be used to identify sector-level challenges and trends.